Ventralax – A cost effective IPOM (IntraPeritonial Onlay Mesh) repair for small umbilical hernias by open method - Edwin, R. Annie Stephy; Ragumani, Ragumani; Ajmal, Imran Thariq (Journal of Neonatal Surgery, 2025)
Background: Both the best surgical technique and the best equipment to employ in this treatment are still up for discussion when it comes to ventral hernias. Owing to the lower cost/efficiency ratio, the open technique is more likely to be used for small size faults. However, laparoscopy yields superior results for medium-sized problems while being more expensive. This study examines the outcomes of a straightforward and successful laparoscopic mesh repair method for small- to medium-sized ventral lesions utilizing the Ventralex® ST patch Method: Between January 1, 2023 and January 31, 2024, 30 patients with ventral primary nonobstructive abdominal wall defects (up to 3 cm) treated laparoscopically using the intraperitoneal onlay mesh repair technique with Ventralex® patch (22 patients) and Ventralex® ST patch (8 patients). Results were prospectively analyzed based on postoperative complications, postoperative pain, recurrent hernia, and quality of life. Results: The technique was used in 30 patients with umbilical hernia (64.5%), patients with juxta-umbilical hernia (19.3%), and patients with epigastric hernia (16.1%). Out of these, 12 patients had nonreducible (nonobstructive) hernia. The median operating time was 55 minutes (range 40–80 min). Minor complications were recorded in 16.1%. The mean hospitalization time was 1.24 days (range 1–2). After a median follow-up of 39 months (range 20–81), the recurrence rate was 11.1% and nil (p = 0.010), and other complaints were recorded in 11.1% and 3.3% of patients (p = 0.293), for Ventralex® patch and Ventralex® ST patch, respectively